The “butterfly wings” and midbrain “V” sign of Artery of Percheron infarction - Chee, Yong Chuan; Abdul Halim, Sanihah (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
An 80-year-old woman with history of hypertension presented to the emergency department following a fall. Her mental status quickly deteriorated and became obtunded. She was stuporous, and unresponsive to verbal stimuli. She had minimally reactive pupils and was moving extremities to painful stimuli. An MRI scan was performed following an unrevealing CT brain.